Is a science-policy nexus void leading to restoration failure in global mining? - Stevens, J.; Dixon, Kingsley (Elsevier Inc., 2017)
The assumption underpinning the US$958 billion global resource sector is continued access to deposits of which an increasing number are targeting pristine, often biodiverse regions of the planet. Regulation of resource access, through leading policy frameworks, is currently based on the expectation that the resource sector has capacity to restore the system to pre-disturbance biodiversity levels despite knowledge voids for most ecosystems. Failure to arrest biodiversity losses is estimated to result in annual economic losses of US$14 trillion by 2050 (CBD, 2014). Here we highlight how the science-policy nexus is currently failing global restoration yet provides the most effective mechanism to overcome capacity limitations and drive scientific innovation to deliver evidence-based decision-making.